When war becomes personal : soldiers' accounts from the Civil War to Iraq - Anderson, Donald, 1946 July 9- (Book collections on Project MUSE., 2008)
Donald Anderson, a former U.S. Air Force officer, has compiled a haunting anthology of personal essays and short memoirs that span more than 100 years of warfare. Alvord White Clements -- himself a veteran of the Second World War -- introduces his grandfather Isaac N. Clements's Civil War memoir; the novelist Paul West writes of his father, a British veteran of World War I, as well as of his own boyhood recollections of the London Blitz. John Wolfe details the life-changing and life-threatening injuries he sustained in Vietnam and the hallucinations he experienced afterward. Second Gulf War veteran Jason Armagost traces his journey to Iraq through the history of literature and the books he brought with him to the war zone. The thirteen essays in When War Becomes Personal tell the enduring truths of battle, stripping away much of the romance, myth, and fantasy. Soldiers more than anyone know what they are capable of destroying; when they write about war, they are trying to preserve the world. -- Publisher's Description.